A novel triazine-rich polymer wrapped MMT: synthesis, characterization and its application in flame-retardant poly(butylene terephthalate). Issue 75 (9th October 2017) - Xin, Fei; Guo, Chao; Chen, Yu; Zhang, Hailong; Qian, Lijun
Abstract : A novel flame retardant (PTAC–MMT) was successfully prepared by wrapping montmorillonite (MMT) with poly(2, 4, 6-triallyloxy-1, 3, 5-triazine) (TAC) via in situ polymerization, and its structure and properties were systematically characterized. Abstract : A novel flame retardant (PTAC–MMT) was prepared by wrapping montmorillonite (MMT) with poly(2, 4, 6-triallyloxy-1, 3, 5-triazine) (TAC) via in situ polymerization, and its structure and properties were characterized by Fourier transformed infrared (FT-IR) spectroscopy, 1 H nuclear magnetic resonance ( 1 H NMR) and 13 C NMR, transmission electron microscopy (TEM), X-ray powder diffraction (XRD) and thermogravimetric analysis (TGA) measurements. The PTAC–MMT and aluminum diethylphosphinate (AlPi) were then incorporated into poly(butylene terephthalate) (PBT) to improve the flame retardancy. The sample containing 1.67 wt% PTAC–MMT and 8.33 wt% AlPi had a LOI value of 36.4% and achieved UL94 V-0 classification. The wrapping flame retardants exhibited excellent anti-dripping effect in PBT composite. This work could provide a novel way to prepare modified MMT and the as-prepared flame retardants.